Posterior Reversible Encephalopathy Syndrome - J Gordon Millichap (Pediatric Neurology Briefs, 2013)
Investigators at Children's Hospital of Montefiore, Albert Einstein College of Medicine, NY, determined the incidence of posterior reversible encephalopathy syndrome (PRES) in a pediatric critical care unit.